Pengaruh Pendidikan dan Pelatihan terhadap Profesionalisme Pegawai Negeri Sipil dalam Pendidikan dan Pelatihan Dinas Pendidikan Kabupaten Bengkalis - Sri Indrastuty; T Jeckie Adrian; Rosmayani Rosmayani (UIR Press, 2019)
Facing the global challenge as one of the efforts to build professional Civil Servants and increase their competence is through Education and Training (Diklat). In Government Regulation No. 101 of 2002 on education and training of civil servant positions, it is mentioned that the implementation of the training is expected to create employee resources that have the necessary competencies to improve the quality of professionalism. This study aims to determine the Effect of Education and Training on Civil Servant Professionalism at the Personnel Board of Education and Training Bengkalis Regency. In order to get a detailed description of the authors using descriptive research method with a quantitative approach. Samples in this study were 52 people Employment Agency Employment Education and Training Bengkalis Regency. Data collection is done through questionnaires. Testing research instrument using validity test and reliability test. Data processing techniques using simple linear regression test, and hypothesis testing to find out how much influence of Education and Training on Civil Servant Professionalism at Bengkalis District Education and Training Personnel Board. The results of this study indicate that the Influence of Education and Training on Civil Servant Professionalism at Bengkalis District Personnel Education and Training Agency categorized Strong. Therefore, efforts must be made by the Agency for Human Resources Education and Training of Bengkalis Regency for Civil Servant Competence at the Office of the Personnel Board of Education and Training of Bengkalis Regency is more optimizing the implementation of Education and Training programs of employees, especially education and functional technical training. Because the training program is very influential on improving the competence of civil service officers of the Education and Training Agency of Bengkalis Regency in particular and Civil Servants of Local Government of Bengkalis Regency in general.